METHODOLOGY OF TEACHING HIGHER MATHEMATICS TO RAILWAY SPECIALTY STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The effective teaching of higher mathematics is an important component of professional training for railway specialty students. Mathematical knowledge forms the basis for understanding technical processes, engineering calculations, transport logistics, automation systems, and railway infrastructure management. However, many students face difficulties in mastering abstract mathematical concepts due to the lack of connection between theoretical material and future professional activities. This article examines modern approaches and methodologies for teaching higher mathematics to railway students. Particular attention is paid to practice-oriented learning, interdisciplinary integration, digital technologies, and competency-based education. The study highlights the importance of adapting mathematical instruction to the specific needs of railway education in order to improve students’ motivation, academic performance, and professional competence.
Keywords: higher mathematics, railway education, teaching methodology, vocational education, engineering mathematics, competency-based learning, digital technologies, interdisciplinary approach.